KONSTRUKSI GENDER DALAM NOVEL-NOVEL ANAK KARYA PENULIS ANAK - Liliani, Else (LITERA, 2015)
Abstract This study aims to describe identities, roles, and gender relations in children’s novels. The data sources were six children’s novels published by Dar! Mizan.The six novels were purposively selected. The data were collected by repeatedly reading the novels, recorded, and classified based on the problem formulation categories. They were analyzed using the framework of feminist literary criticism, namely woman as a reader. The results of the study are as follows. First, gender equality has not been manifested because there is still gender identity stereotyping. Characters with two identities, feminine and masculine, are described as weird characters. Second, there is inequality in the distribution of gender roles. Female characters have roles in public and domestic sectors and male characters play roles in the public sector only. Third, existing relations show varied but recognizable patterns. The relations are manifested in different forms depending on contexts, sexes, ages, social classes, cultures, and descendant factors.